The time of the therapeutic communities : people, places and events - Clarke, Liam, 1946- (Therapeutic communities, 2004)
From the 1950s onwards different movements, ideas and key figures have contributed to the emergence of the initiative which is now recognised as Therapeutic Communities. This book follows these post-war changes (such as 'libertarianism' and the 'open door movement') through to the present day and discusses the influence they had on the practice of psychiatry and the introduction of Therapeutic Communities. Including chapters on the lives, work and influence of Joshua Bierer and R.D. Laing, as well as providing an explanation of the Villa 21 project (the only attempt to apply Laingian concepts.